Предмет: Математика,
автор: dimka33331
упрастите:
1) (3x-2)^{2}-3(6x-3) 6x+3
2) (5x-4)^{2}-(5x+7) 5x-7
Ответы
Автор ответа:
0
1)(3x-2)²-3(6x-3)(6x+3)=9x²-12x+4-3(36x²-9)=9x²-12x+4--108x²+27=-99x²-12x+31
(3x-2)²-3(6x-3)6x+3=9x²-12x+4-108x²+54x+3=-99x²+42x+7
2)(5x-4)²-(5x+7)(5x-7)=25x²-40x+16-25x²+49=-40x+65
(5x-4)²-(5x+7)5x-7=25x²-40x+16-25x²-35x-7=-75x+9
(3x-2)²-3(6x-3)6x+3=9x²-12x+4-108x²+54x+3=-99x²+42x+7
2)(5x-4)²-(5x+7)(5x-7)=25x²-40x+16-25x²+49=-40x+65
(5x-4)²-(5x+7)5x-7=25x²-40x+16-25x²-35x-7=-75x+9
Похожие вопросы
Предмет: Математика,
автор: Kakaka54
Предмет: Математика,
автор: kolans590
Предмет: Биология,
автор: Аноним
Предмет: История,
автор: O6lechkasnik